"That's well good": A Re-emergent Intensifier in Current British English. (March 2021) - Aijmer, Karin
Well has a long history and is found as an intensifier already in older English. It is argued that diachronically well has developed from its etymological meaning ('in a good way') on a cline of adverbialization to an intensifier and to a discourse marker. Well is replaced by other intensifiers in the fourteenth century but emerges in new uses in Present-Day English. The changes in frequency and use of the new intensifier are explored on the basis of a twenty-year time gap between the old British National Corpus (1994) and the new Spoken British National Corpus (2014). The results show that well increases in frequency over time and that it spreads to new semantic types of adjectives and participles, and is found above all in predicative structures with a copula. The emergence of a new well and its increase in frequency are also related to social factors such as the age, gender, and social class of the speakers, and the informal character of the conversation.